Marked QTc Prolongation and Torsades de pointes in Patients with Chronic Inflammatory Arthritis - Lazzerini, Pietro Enea; Capecchi, Pier Leopoldo; Bertolozzi, Iacopo; Morozzi, Gabriella; Lorenzini, Sauro; Simpatico, Antonella; Selvi, Enrico; Bacarelli, Maria Romana; Acampa, Maurizio; Lazaro, Deana; El-Sherif, Nabil; Boutjdir, Mohamed; et al. (Frontiers in Cardiovascular Medicine, 2016)
Mounting evidence indicates that in chronic inflammatory arthritis (CIA), QTc prolongation is frequent and correlates with systemic inflammatory activation. Notably, basic studies demonstrated that inflammatory cytokines induce profound changes in potassium and calcium channels resulting in a prolonging effect on cardiomyocyte action potential duration (APD), thus on the QT interval on the electrocardiogram. Moreover, it has been demonstrated that in RA patients the risk of SCD is significantly increased when compared to non-RA subjects. Conversely, to date no data are available about Torsades de Pointes (TdP) prevalence in CIA, and the few case reported considered CIA only an incidental concomitant disease, not contributing factor to TdP development. We report three patients with active CIA developing marked QTc prolongation, in two cases complicated with TdP degenerating to cardiac arrest. In these patients, a blood sample was obtained within 24h from TdP/marked QTc prolongation occurrence and levels of IL-6, TNF-alpha and IL-1 were evaluated. In all three cases, IL-6 was markedly elevated, ~10 to 100 times more than reference values. Moreover, one patient also showed high circulating levels of TNF-alpha and IL-1. In conclusion, active CIA may represent a currently overlooked QT-prolonging risk factor, potentially contributing in the presence of other “classical” risk factors to TdP occurrence. In particular, a relevant role may be played by elevated circulating IL-6 levels via direct electrophysiological effects on the heart. This observation should be carefully kept in mind, particularly when recognizable risk factors are already present and/or the addition of QT-prolonging drugs is required.